The persistence of deltamethrin in Malaysian agricultural soils - Ismail, B.S.; Mazlinda, M.; Tayeb, M.A. (Universiti Kebangsaan Malaysia, 2015)
Studies on the persistence and dissipation of deltamethrin (C22H19Br2NO3) in two types of soil, namely peat and silty clay were conducted under laboratory conditions. The analysis was done using a gas chromatography (GC) equipped with an electron capture detector (ECD). The dissipation rate of deltamethrin was faster in silty clay soil than in peat soil at 25°C. When the temperature was increased from 25 to 35°C, the half-life of deltamethrin decreased by 32.53% in peat soil and 22.9% in the silty clay soil in the presence of light. When the same experiment was conducted in the dark, the decrease in the half-life of deltamethrin was 27.9% in peat soil and 22.5% in silty clay soil. When the soil moisture content was increased from 40 to 60%, the half-life of deltamethrin decreased by 50.7 and 19.75% in peat soil and silty clay soil, respectively. A significant degradation rate of deltamethrin was observed in non-autoclaved soil compared with that in autoclaved soil where the half-life was reduced by 76.05% in peat soil and 59.21% in silty clay soil. The results showed that the degradation rate of deltamethrin in soil had a direct relationship with the microbial activity in the soil.